Analisis Hubungan antara Kadar Sulfur Total dan Gross Calorific Value Menggunakan Metode BS/ISO di Laboratorium Penanganan dan Pengangkutan Batubara PT Bukit Asam Tbk - Yuswilia, Salsabilla; Mawardi, Mawardi (Lembaga Yasin AlSys, 2025)
The quality of coal is significantly influenced by its sulfur content and calorific value, two key parameters in determining energy efficiency and environmental impact. This study aims to analyze the relationship between total sulfur content and gross calorific value (GCV) in coal samples collected from three different locations at PT Bukit Asam Tbk. Sulfur analysis was conducted using a LECO S632 instrument in accordance with the BS ISO 19579:2006 standard, while calorific value was measured using a Parr 6200 bomb calorimeter based on the BS ISO 1928:2020 standard. Analysis of nine samples showed that sulfur content ranged from 0.20% to 0.91%, while final GCV values ranged from 5.790 to 7.772 cal/g. Adjustments for sulfur and acid content resulted in an average decrease in calorific value of 10.3 cal/g. Regression analysis revealed a moderately positive correlation between sulfur content and calorific value, with a coefficient of determination (R²) of 0.4194. Although sulfur in the form of pyrite can contribute energy during combustion, its presence must still be controlled due to the harmful emissions it generates. These findings underscore the importance of sulfur regulation in maintaining energy efficiency and coal quality in line with industry standards.